Public Space and the Coevolution of Digital and Digitized Media - Finneman, Niels Ole (MedieKultur: Journal of media and communication research, 2006)
In the first section it is argued that digital media are characterized by a variable functional architecture. In the second section, it is argued that theories af replacement and convergence ought to be replaced by a theory of coevolution in order to understand how the internet and mo-bile media are integrated in different societies. The third section discus-ses whether the influence of the old media in this coevolutionary pro-cess also implies that differences in the existing media systems will lead to different developments in the internet.